Health and Safety Risk Levels in High-Rise Buildings - Sobirin, Muhamad; Priyomarsono, Naniek Widayati; Susilo, Alfred Jonathan (Migration Letters, 2023)
Construction projects are jobs that have a high risk of work accidents with the possibility of severe consequences of work accidents. Construction activities have various risks, including occupational safety and health (OHS) risks, as the construction process requires a lot of labour and involves heavy equipment. Hence, it has the potential level of construction OHS risk to the danger of work accidents. From the data search to the office (PUPR) of the Sub-Department of Bina Konstruksi, related to the data, researchers to the Sub-Coordinator of Construction Services Development discussed the basis of the value of the frequency of occurrence of construction OHS risks; he said that the basis was from several associations invited to the office, to discuss OHS risks, then the values arose, namely 1, 2 and 3, there was no analysis of the calculation referring to these values. The basis of Per-Men of Public Works No. 5 of 2014 issued a frequency value. The objectives of this study are: To find the limit of the frequency value of the occurrence of types of OHS risks to complement Per-Men of Public Works No. 5 / 2014 and can classify contractors for the level of OHS risk in various high-rise buildings, both BUMN contractors and private contractors throughout Indonesia. The method in this study uses Mamdani fuzzy because this method is more widely used because it has intuitive advantages, has been commonly used in various scientific fields, and is suitable for conducting an environmental analysis. The resulting output is dynamic because the data to be used is in the form of values/numbers, while in fuzzy rules, there needs to be input data in the form of numbers because the output results are also numbers. Besides that, in the questionnaire given to respondents, the answers are in the form of varied values/numbers; it seems appropriate to analyse these numbers using fuzzy logic. Based on the analysis results, the lowest value is 2.65, while the highest is 7.26. Then the limit value of the frequency of occurrence of the type of construction OHS risk for the value "Rarely" is = 0-2.65, and the value "Sometimes" is = 2.66 -7.99, while for the value "Often" is> 7.99. Furthermore, the novelty in this research is to complement Per-Men of Public Works No. 5/2014, namely the limit of frequency value: 5/2014, namely the limitation of frequency value.